METODE KOAGULASI DAN ELEKTROKOAGULASI DENGAN PENAMBAHAN HIDROGEN PEROKSIDA PADA PROSES PENGOLAHAN LIMBAH CAIR BUANGAN LAUNDRY - Bambang Hari Prabowo; Hendriyana Hendriyana; Lulu Nurdini; Mutiara C. Firdaus; Tengku Leinaldy P. (Eksergi, 2019)
Problems with laundry waste, especially in the content of surfactants in detergents. Surfactants have properties as surface tension reducers. In the body of water can cause foam that can mediate itching. As domestic waste, this laundry waste is generally disposed directly to the environment without any treatment, which if left unchecked, of course, will be bad for the environment. The content in laundry wastes such as COD, BOD, TDS, pH, phosphate level and turbidity that do not comply with quality standards can cause polluted environments and can disrupt public health and the environment. In this study, two water treatment methods were applied, namely coagulation and electrocoagulation by adding 7 ml of 5% peroxide. This research was carried out in a batch process both electrocoagulation and coagulation. The parameters reviewed were COD, TSS, pH, phosphate level, PO4- and turbidity. Coagulation using alum coagulant (Aluminum sulfate). The variation of the two coagulation processes is, for coagulation, the stirring speed is 300 rpm for 10 minutes and the coagulant dose (500 ppm, 600 ppm, 700 ppm, 800 ppm and 900 ppm). In electrocoagulation contact times were varied (15 minutes, 20 minutes, 25 minutes, 30 minutes). The best results obtained were wastewater treatment using the Electrocoagulation method with a COD reduction of 76%, BOD 83%, turbidity 98% and phosphate 99.9%.